Potential Use of Left Renal Vein Graft in Pancreaticoduodenectomy Combined with Long Segmental Resection of the Superior Mesenteric-Splenic-Portal Vein Confluence - Choi, Sung Hoon; Hwang, Ho Kyoung; Kang, Chang Moo; Lee, Woo Jung (JOP. Journal of the Pancreas, 2011)
Context Various techniques for reconstruction after superior mesenteric-splenic-portal vein confluence resection during pancreaticoduodenectomy have been introduced. A certain kind of vascular grafting may be necessary especially when long segmental resection of superior mesenteric-splenic-portal vein confluence is required. Case report we herein report the cases of two patients who underwent left renal vein grafting in a pancreaticoduodenectomy with combined resection of the long segment of the superior mesenteric-splenic-portal vein confluence for pancreatic head cancer following neoadjuvant concurrent chemoradiation therapy as well as their long-term outcomes with graft patency without deterioration of renal function. Conclusion Our experience with these two cases indicates that an autologous interposition graft using the left renal vein may be considered a safe and convenient conduit in the case of long segmental resection of the superior mesenteric-splenic-portal vein confluence during a pancreaticoduodenectomy following preoperative neoadjuvant chemoradiation therapy. Image: Postoperative follow-up of BUN and serum creatinine levels.